The effects of silage additives on the feeding value of forage sorghum silage - Ward, G.M.; Smith, E.F.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This experiment was to determine effects from adding glucose, sucrose and starch to forage sorghum (DeKalb FSla) immediately prior to ensiling, on the feeding value of the subsequent silage. When the forage sorghum grain was at medium-to-hard dough stage, it was field chopped with a conventional silage cutter. Dry matter the forage was determined at harvesting and equalized by adding water. Each additive was added to the forage prior to ensiling. The sorghum forage was ensiled in 40-ton concrete stave silos.
Keywords: Beef; Silage additives; Forage sorghum silage; Ensiling